Pathogenesis of Biliary Cirrhosis and Modern Clinical Diagnostic Methods - Shoymardonovich, Namozov Begali (American Journal of Bioscience and Clinical Integrity, 2025)
General Background: Cirrhosis is the final stage of liver fibrosis, characterized by significant structural disruption due to the formation of regenerative nodules and excessive fibrous tissue. It remains a major global health concern due to its chronic progression and potential complications. Specific Background: In developed countries, cirrhosis is primarily caused by chronic alcohol consumption, viral hepatitis B and C, or metabolic-associated fatty liver disease (MAFLD). In Asia and Africa, chronic hepatitis B remains the leading cause. Complications such as portal hypertension and hepatic encephalopathy significantly impact patient prognosis. Knowledge Gap: Cirrhosis has traditionally been diagnosed through clinical evaluation and imaging techniques. However, there is still a pressing need for more precise, non-invasive diagnostic markers and targeted treatment strategies to slow disease progression. Aims: This study explores the mechanisms, clinical presentation, and modern diagnostic approaches of biliary cirrhosis to improve early detection and management. Results: The findings highlight the complex interactions between growth factors, cytokines, and intrahepatic blood flow patterns in the formation of regenerative nodules. Angiogenesis plays a crucial role in the development of portal hypertension, worsening disease severity. Accurate diagnosis continues to rely on laboratory tests, advanced imaging techniques such as transient elastography and MRI elastography, and selective liver biopsy. Novelty: This review provides an updated analysis of the causes and diagnostic advancements in biliary cirrhosis, with a particular focus on emerging non-invasive imaging techniques. Implications: The study underscores the importance of early diagnosis, routine screening for hepatocellular carcinoma, and comprehensive treatment strategies to reduce complications and improve patient outcomes.